2021
DOI: 10.3389/fcell.2021.643043
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Kinase-Driven Networks of Novel Long Non-coding RNAs and Their Molecular Targets in Myeloproliferative Neoplasms

Abstract: Recent research has focused on the mechanisms by which long non-coding RNAs (lncRNAs) modulate diverse cellular processes such as tumorigenesis. However, the functional characteristics of these non-coding elements in the genome are poorly understood at present. In this study, we have explored several mechanisms that involve the novel lncRNA and microRNA (miRNA) axis participating in modulation of drug response and the tumor microenvironment of myeloproliferative neoplasms (MPNs). We identified novel lncRNAs vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Importantly, IL-8 released by BM-MSCs can promote the adhesion and migration of malignant cells, enhancing their survival (76). Wong and colleagues recently demonstrated that K562-derived sEVs carrying the long non-coding RNA LNC000093 and the microRNA miR-675-5p regulate vascular endothelial growth factor (VEGF) expression in BM-MSCs (77), coinciding with the previously described angiogenic ability and high level of VEGF in CML patient plasma that contribute to the tumorigenic niche (78). The growth-suppressive miR-320 is selectively sorted in CML EVs by RNA binding protein heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), transferred to BM-MSCs and inhibits b-catenin, thereby hindering osteogenesis, remodeling of the BM niche and promoting CML progression (79).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Importantly, IL-8 released by BM-MSCs can promote the adhesion and migration of malignant cells, enhancing their survival (76). Wong and colleagues recently demonstrated that K562-derived sEVs carrying the long non-coding RNA LNC000093 and the microRNA miR-675-5p regulate vascular endothelial growth factor (VEGF) expression in BM-MSCs (77), coinciding with the previously described angiogenic ability and high level of VEGF in CML patient plasma that contribute to the tumorigenic niche (78). The growth-suppressive miR-320 is selectively sorted in CML EVs by RNA binding protein heterogeneous nuclear ribonucleoprotein A1 (hnRNPA1), transferred to BM-MSCs and inhibits b-catenin, thereby hindering osteogenesis, remodeling of the BM niche and promoting CML progression (79).…”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…In renal cancer, miR-549a was found to be reduced and such lower levels were reflected in the derived exosomes that were taken up by endothelial cells and the reduced miR-549a levels resulted in de-repression of HIF-1α and VEGF ultimately leading to increased angiogenesis [ 78 ]. In support of an interplay between lncRNAs and the miRNAs, lncRNA LNC000093 was found to be downregulated while the miRNA it sponged, miR-675, is elevated in imatinib-resistant leukemia cells [ 79 ]. In summary, it is increasingly being realized that exosomes, through their epigenetic cargo, induce resistance against multiple TKIs in different human cancers ( Table 4 ).…”
Section: Mechanisms Of Exosome-mediated Cancer Drug Resistancementioning
confidence: 99%
“…Numerous intratumoral T-cells are also present in the TME of the lymphoma, representing a very heterogeneous group of immune cells composed of various subpopulations: regulatory T cells (Treg), helper T cells (Th), CD8 + T cells, and follicular helper T cells (TFH) [99]. Although the specific role of these T cells in tumorigenesis is very complex and not yet entirely clear, several studies have shown that they not only induce tumor progression through the release of cytokines and/or direct contact with them, but they also play a key role in immunosuppression, and activation of the antitumor immune response-thereby promoting an immuno-proprietary microenvironment [57,100].…”
Section: Lymphomagenesis and Tumor Microenvironmentmentioning
confidence: 99%